The Effect of Logic Concept Cognitive Development on Physics Science Learning Achievement with Problem Solving Approach of the Eighth Grade Students of SMP Negeri 16 Palu - Wirdha, Wirdha; Hatibe, Amiruddin; Darsikin, Darsikin (Jurnal Riset Pendidikan MIPA, 2017)
This research aims to find out the effect of logic concept mastery by cognitive development on physics science learning achievement with a problem-solving approach. The population of subjects was students of class VIII SMP Negeri 16 Palu with purposive sampling technique with a quasi-experimental method based on the results of data analysis can be concluded as follows: 1) oriented learning with a problem-solving approach to learning in the subject matter in class VIII of SMP can light improve student learning outcomes;Â  2) there was a significant effect between mastery of the concept of cognitive development to the learning outcomes with the value of R= 0.802; 3) the response of the student to the teaching component that includes teaching materials, LKS, practice, and approaches used by the teacher in teaching was happy and interested.